Морфофункціональний стан жіночої репродуктивної системи за умов застосування наночастинок срібла - Литвиненко, Аліна; Ступчук, Марія; Блашків, Орест; Вознесенська, Тетяна; Lytvynenko, Alina; Voznesenskaja, Tetyana; Blashkiv, Orest; Stupchuk, Mariya (Східноєвропейський національний університет імені Лесі Українки, 2016)
За умов одно-, п’яти- та десятикратного внутрішньовенного введення наночастинок срібла (2 мг/кг та 4 мг/кг) оцінювали мейотичне дозрівання ооцитів, а також за умов десятикратного внутрішньовенного введення наночастинок срібла (2 мг/кг та 4 мг/кг) – пре- й постімплантаційну смертність ембріонів у мишей.Дослідження (дві серії) проведено на самках білих лабораторних мишей восьми тижнів (16–18 г). Вико- ристовувані наночастинки срібла (AgNPs, 30 нм, концентрація – 8 мг/мл за металом, форма – сферична). Уперше отримано дані про те, що однократне й п’ятикратне введення AgNPs (2 мг/кг, 4 мг/кг) не викликає запалення, не впливає на ооцити, змінює функціональний стан фолікулярних клітин і скоротливість матки. 10-кратне введення AgNPs (2 мг/кг, 4 мг/кг) приводить до розвитку запальної реакції й пригнічує оваріальну функцію (формування полярного тільця ооцитів, збільшує кількість апоптотичних і некротичних клітин у фолікулярному оточенні ооцита), змінює функціональний стан матки (зростає скоротливість оваріального й цервікального відділів матки), проте не впливає на розвиток пре- й постімплантаційних ембріонів. Ключові слова: ооцити, матка, ембріони, наночастинки срібла. The effect of AgNPs on mammalian cells and tissues requires further study. The effect of AgNPs on the functional status of the female reproductive system of mammals has not been examined yet.The aim is under condition of the intravenous treatment of silver nanoparticles (AgNPs) to estimate the functional status of the reproductive system in female mice, namely to assess meiotic maturation of oocytes, viability of follicular cells surrounding the oocyte, spontaneous contractile activity of the myometrium and pre-and postimplantation mortality of embryos. Research (two series) has been done on white laboratory 8 weeks (16–18 g) mice female in compliance with all requirements for work with laboratory animals (International European Convention for the Protection of Vertebrate Animals, Strasbourg, 1986). First series. AgNPs are spherical nanoparticles of 30 nm (8 mg/ml for metal) diluted in water for injection. Method of treatment: intravenous. It has been investigated two doses of 2 mg/kg and 4 mg/kg. Frequency of treatment: one time per day of each dose of 1, 5 and 10 times (n = 8 animals in each group). Control animals injected with saline. Material for the study (ovaries, uterus) were taken the day after the last AgNPs injection. Oocytes cultivation. The oocytes have been isolated mechanically from the ovaries of mice in a non-enzymatic way (without cumulus cells and in cumulus-oocyte-cell complexes). The mice oocytes from one group were collected and distributed into separate chambers, 10–20 oocytes each. All control and experimental oocytes were cultured under the same conditions (a sterile box, cameras with 0.4 ml culture medium DME and 15 mM HEPES, Ca2+ concentration of 1,71 mM, temperature 37° C, duration 20 hours). Morphological study of oocytes was performed under a microscope MBS- 10 after 2 hours of cultivation (% of total): the oocytes which restored the meiotic maturation (BM) and were at metaphase I stage (germinal vesicle break-down), and after 20 hours were at metaphase II stage (completed by the first division of meiosis and formed the first polar body (PB)) and oocytes with atypical morphology (unevenly granulated cytoplasm and fragmentation characteristics of the latter) have been counted. Method color fluorescent dyes. The estimation of apoptotic and necrotic death of follicular cells was performed by morphological characteristics using the method of in vivo dual-color fluorescent dye nucleic acids Hoechst 33 342 and propidium iodide. Morphological studies were performed using a fluorescent microscope with water-immersion at х85. There has been used a video system sending the image from the microscope to the computer. The percentage of the living, apoptotic and necrotic cells has been determined by counting at least 200 cells. The method of phase-graphical analysis in the study of the contractile activity of the uterine myometrium. To investigate the contractile activity of the ovarian (OD) and cervical (CD) uterine myometrium departments the method of phase-graphic analysis has been used (Gullam J., Blanks A., Thornton S., Shmygol A. 2009). To characterize the spontaneous emission by quantity of the following parameters contractile activity were taken into consideration: amplitude of reduction (mN), frequency of reduction (number per second), duration of contraction and relaxation (sec), speed reduction and relaxation (mN/second); index of contractility («IC» index of contractility, was calculated as the product of Fmax on CVmax/RVmax, mN). Strips of uterine myometrium have been separated from the connective tissue under the microscope MBS-10 and transferred to Krebs solution (4оС). To register isometric force of reduction agents and CD myometrium of the uterus, which was being cut off with the endometrium along the uterine horns (up to 10 mm and a width of less than 1 mm to 4 from one horn), transferred into the camera and fixed. The Krebs solution (37оС, pH 7,29) was used as perfusion solution in a camera. The force of isometric contractions was recorded using the high-speed recorder. Uniformity of preparation perfusion with washing solutions was provided by the peristaltic pump НП-1М. Second series. There has been investigated the effect of AgNPs on pre- and post-implantation embryo mortality. Groups of animals: 1 – control (n = 10), 2 – AgNPs (2 mg/kg, n = 10), 3 – AgNPs (4 mg/kg, n = 10). Fetal mortality in mice. Female control and experimental groups crossed with intact males. Counted: A - number of live embryos; B – number of seats of resorption (number of dead embryos); B – number of corpora lutea of pregnancy. Indicators of pre-and post-implantation death was calculated using the formula: ((B-A + B) / B) • 100 % and (B / (A + B)) • 100 %. Statistical analysis. For the statistical analysis of the results the software package Origin 8Pro (OriginLab Corp., North., MA, USA) and spreadsheets «Microsoft®Excel2003» have been used. The reliability of the difference of mean values determined by Student’s t-test, considering to be reliable the values of p <0,05. The statistical analysis of the results of research conducted by using analysis of variance ANOVA followed by comparison of mean values between groups by Newman-Coles test using the statistic program-6. Results. Established that single input and five-time AgNPs treatment (2 mg/kg, 4 mg/kg) does not cause inflammation and does not affect oocytes but changes follicular cells functional state and alters functional state of the uterus. Ten-time AgNPs treatment (2 mg/kg, 4 mg/kg) inhibits the formation of ocyte first polar body in vitro, increases the number of apoptotic and necrotic cells in follicular environment of oocyte), changes the functional state of the uterus (increasing contractility of ovarian and cervical uterus departments), but does not affect the development of pre- and postimplantatsiynyh embryos but does not affect the development of pre- and postimplantation embryos. Using AgNPs different sizes and with different coatings further studies are needed for the elucidation of mechanisms underlying exposure AgNPs in germ and somatic cells.
Functional Status of Reproductive System Under Treatment of Silver Nanoparticles in Female Mice
Keywords: ооцити; наночастинки срібла; ембріони; матка; oocytes; AgNPs; embryos; uterus